Candidatus Neoehrlichia mikurensis is widespread in questing Ixodes ricinus ticks in the Czech Republic - Ondruš, Jaroslav; Balážová, Alena; Baláž, Vojtech; Zechmeisterová, Kristína; Novobilský, Adam; Široký, Pavel (Ticks and tick-borne diseases, 2020)
Candidatus Neoehrlichia mikurensis, the causative agent of tick-borne "neoehrlichiosis" has recently been reported in humans, mammals and ticks in Europe. The aim of this study was to map the distribution of this bacterium in questing ticks in the Czech Republic. A total of 13,325 Ixodes ricinus including 445 larvae, 5270 nymphs and 7610 adults were collected from vegetation by flagging in 140 Czech towns and villages from every region of the Czech Republic. The ticks were pooled into 2665 groups of 5 individuals respecting life stage or sex and tested for the presence of Ca. Neoehrlichia mikurensis by conventional PCR targeting of the groEL gene. The bacterium was detected in 533/2665 pools and 125/140 areas screened, showing an overall estimated prevalence of 4.4 % in ticks of all life stages. Phylogenetic analysis revealed only small genetic diversity among the strains found. Two pools of questing larvae tested positive, suggesting transovarial transmission. According to this study, Ca. Neoehrlichia mikurensis is another tick-borne pathogen widespread in I. ricinus ticks in the Czech Republic.
Keywords: Nymph; Ixodes; larva; Female; klíště; Tick-borne disease; zvířata; genetická variace; Genetic Variation; nymfa; ženské pohlaví; Male; Czech Republic; Ixodes ricinus; Larva; Animals; Anaplasmataceae; Česká republika; mužské pohlaví; Candidatus Neoehrlichia mikurensis